Evidence for five divergent thioredoxin h sequences in Arabidopsis thaliana. - Rivera-Madrid, R (1995)
Five different clones encoding thioredoxin homologues were isolated from Arabidopsis thaliana cDNA libraries. On the basis of the sequences they encode divergent proteins, but all belong to the cytoplasmic thioredoxins h previously described in higher plants. The five proteins obtained by overexpressing the coding sequences in Escherichia coli present typical thioredoxin activities (NADP(+)-malate dehydrogenase activation and reduction by Arabidopsis thioredoxin reductase) despite the presence of a variant active site, Trp-Cys-Pro-Pro-Cys, in three proteins in place of the canonical Trp-Cys-Gly-Pro-Cys sequence described for thioredoxins in prokaryotes and eukaryotes. Southern blots show that each cDNA is encoded by a single gene but suggest the presence of additional related sequences in the Arabidopsis genome. This very complex diversity of thioredoxins h is probably common to all higher plants, since the Arabidopsis sequences appear to have diverged very early, at the beginning of plant speciation. This diversity allows the transduction of a redox signal into multiple pathways.